Dampak Belajar Online Menulis Bahasa Arab dengan Berpikir Kreatif Masa Covid-19 - Ade Destri Deviana (Al-Falah: Jurnal Ilmiah Keislaman dan Kemasyarakatan, 2021)
The purpose of this study was to determine the impact of online learning of Arabic writing materials (kitabah) with creative thinking during the covid-19 period. In general, online learning is good, but to find out students' views on the reality of learning during COVID-19 in terms of impact. The research method used is descriptive qualitative to 110 active students from classes A, B, and C Semester V 2019-2020 Academic Year majoring in Arabic Language Education STIQ Amuntai South Kalimantan. The result of the study is to explain the impact of online learning of Arabic writing material (kitabah) with creative thinking during the Covid-19 period, there are 2 categories, namely the category of the impact of learning strategies and the category of the impact of learning experiences. The impact of the learning strategy is in the form of learning by analyzing and completing tasks with sufficient time, network preparation, role models, note-making, time management, learning environment, following the direction of lecturers, attending online seminars, active learning, self-evaluation. The impact of the learning experience are independent learning, familiarization with technology, repetition, decreased motivation and interest in learning, unstable network conditions, more efficiency. From this impact, students and lecturers hope that the learning process can be carried out in the classroom. Keywords: Impact, Online Learning, Writing, Creative Thinking, Covid-19